Development and validation of a prognostic nomogram for unresectable pancreatic ductal adenocarcinoma with synchronous liver metastases: a study based on the SEER database and an external cohort - Huan, Lu; He, Qi; Cao, Yang; Liu, Changan; Li, Yue (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma with synchronous liver metastases (PDACLM) represents a highly aggressive malignancy with limited treatment options and poor prognosis. While conversion therapy may enable curative surgery in a small subset of patients, the majority ultimately remain ineligible for resection. Prognostic tools tailored to this unresected population are lacking but urgently needed for guiding clinical decisions.MethodsWe conducted a retrospective cohort study using 9,469 patients with histologically confirmed PDACLM from the SEER database (2010–2015), supplemented by an external validation cohort of 94 patients treated at the Second Affiliated Hospital of Chongqing Medical University (2020–2023). Multivariate Cox regression analysis was used to identify independent prognostic factors. A nomogram was constructed and validated internally and externally to predict individualized overall survival (OS) at 12, 18, and 24 months.ResultsAge ≥65 years, higher tumor grade, and undetermined nodal status were independently associated with reduced OS, while chemotherapy, radiotherapy, and metastasis-directed surgery significantly improved survival outcomes (all P<0.05). The nomogram demonstrated good discriminative performance with a C-index of 0.73 in the training cohort and 0.72 in internal validation. External validation showed consistent predictive accuracy (C-index: 0.715). Calibration plots and decision curve analyses supported the model’s reliability and clinical utility.ConclusionWe developed and externally validated a clinically accessible nomogram for survival prediction in unresected PDACLM patients. This tool may assist clinicians in risk stratification and treatment planning for a frequently overlooked patient subgroup. Further prospective validation is warranted to confirm its applicability in broader clinical settings.